Directions of Capital Flows in Contemporary International Monetary System - Janicka, Małgorzata (Studia Oeconomica Posnaniensia, 2017)
Directions and the volume of investment capital flows in the global economy are inherently linked with circumstances surrounding the international monetary system. The neoclassical model, the main point of reference for economists who presently examine international capital flows, can hardly be considered an appropriate research tool. It does not take account the specificity of the contemporary monetary system, neither can it explain two-direction flows that have currently dominated the global economy. Capital does not flow from surplus, developed and rich countries with substantial financial resources to deficit countries, developing and poor, which suffer from capital shortage. The contemporary currency system developed an operational framework, which has enabled developed countries to become net debtors and developing countries to become net creditors. Studying the so called Lucas paradox or contemporary international capital flows using the neoclassical model, which oversimplifies the reality, has become little justified.